Kemandirian Energi dan Pangan Berbasis Potensi Pedesaan Melalui Aliansi Strategis dengan Perguruan Tinggi Pertanian Daerah - Meidi Syaflan; Andi Afrizal; Nadime Lasykar Muhammad (Universitas Muhammadiyah Purworejo, 2016)
The strategic alliance was built between the Center for Biogas and Bioslurry Development, Department of Agricultural Product Technology, Fateta Instiper Yogyakarta and CV. Bina Energi Mandiri Persada, Biodigester Blue Biodigester developer partner SNI 7826: 2012 since 2013 has succeeded in building 250 units in DIY which are capable of producing methane gas as an energy source and bioslurry as organic fertilizer and raw material to support upstream agricultural businesses. The regional approach clustering shows that it is concentrated in 8 hamlets with a total of 113 units and the rest is spread out because the number is less than 7 units/hamlet.Study on optimizing the benefits of the biodigester to build a village that is independent of energy and food based on local potential in the cluster qualitatively with a simple test of the cluster response speed to further development plans to explore the emotional closeness of cluster members and the ease of forming alliances with outside parties. Only one cluster responded positively to the development plan and quickly built an alliance with the village government to create an energy and food independent village, supported by the establishment of BMT. The orientation of the biodigester as an energy producer turned out to cause the other 7 clusters to be unenthusiastic in welcoming the development plan because they could not optimize bioslurry properly due to limitations and land conversion. Clusters that respond positively and easily build alliances can be developed as energy and food independent areas, while the other 7 clusters are aimed at optimizing the use of biogas for the home industry and bioslurry as raw material for feed and liquid organic fertilizer. To ensure the availability of raw materials in the upstream sector of biodigester development, it is time to build a strategic alliance with regional agricultural universities in areas with rural areas with low land conversion rates.